2018
DOI: 10.4193/rhinol/18.010
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the inferior turbinate using 3D geometric morphometrics: an anatomical study and discussion of the potential clinical implications

Abstract: Background: The inferior turbinate is probably the most important anatomical structure within the nasal airway. However, relatively little is known concerning its 3D anatomy. Complete removal of the IT may lead to severe functional disorders and reconstruction is often necessary. Methods: We performed an anatomical study using modern 3D reconstruction tools (Amira 5.4.2 software). The study was conducted on 200 inferior turbinates obtained from CT-scanned images. Metric and morphological analyses were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Yet, to the best of our knowledge, no attempt to investigate quantitative differences in turbinate size and shape between geographically diverse populations has actually been undertaken. Rather, the few previous attempts to quantify turbinate morphology have focused on age‐ and sex‐related differences within a single population (Balbach et al, ; de Bonnecaze et al, ; Lang & Baumeister, ; Lang & Sakals, ; San, Muluk, Saylisoy, Acar, & Cingi, ; Uzun et al, ), with most failing to demonstrate significant differences across adult age groups or between males and females in the population investigated. For example, Balbach et al () measured the height, length, and breadth of the bony inferior turbinate in a sample of male and female German patients and found no significant differences between the two sexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, to the best of our knowledge, no attempt to investigate quantitative differences in turbinate size and shape between geographically diverse populations has actually been undertaken. Rather, the few previous attempts to quantify turbinate morphology have focused on age‐ and sex‐related differences within a single population (Balbach et al, ; de Bonnecaze et al, ; Lang & Baumeister, ; Lang & Sakals, ; San, Muluk, Saylisoy, Acar, & Cingi, ; Uzun et al, ), with most failing to demonstrate significant differences across adult age groups or between males and females in the population investigated. For example, Balbach et al () measured the height, length, and breadth of the bony inferior turbinate in a sample of male and female German patients and found no significant differences between the two sexes.…”
Section: Introductionmentioning
confidence: 99%
“…San et al () also investigated sexual dimorphism using inferior turbinate area in a Turkish sample, and similarly found no significant differences between males and females after 25 years of age. Most recently, de Bonnecaze et al () used a geometric morphometric method employing five coordinate landmarks to assess size and shape differences across three age groups (<30, 30–60, >60 years) and between sexes in a sample of French individuals. These authors also found minimal evidence of sexual dimorphism, but they did note the oldest age group exhibited slightly reduced turbinate curvature, which they attribute to reduced osseous density.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted using CT also reported that there were no significant age-related linear dimensional changes in ITH [ 34 ]. Similarly, no gender-related variation was observed in a study conducted by de Bonnecaze et al while evaluating three-dimensional polymorphism of the inferior turbinates [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study there was no significant difference in the gender distribution of the total turbinate volume. In a recently published CT based study conducted to evaluate three dimensional (3D) polymorphism of the inferior turbinates, no gender dimorphism was observed ( de Bonnecaze et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%